Dysfluencies in Nopnals Under D.A.F:1 - NP, Nataraja; MV, Ramesh; Pandita, Raj Kumar (Journal of All India Institute of Speech and Hearing)
Lee (1950), showed that experimentally produced delay in air-conducted auditory feedback of speech causes widespread speech disruption. Primarily, delayed auditory feedback (DAF) produces a slower rate of speech, dysfluencies and articulatory errors (Lee, 1950, 1951; Black 1951; Fairbanks and Guttman,1951). Lee (1950, 1951) has given the term ’Artificial Stutterer’ to a person speaking under delayed auditory feedback. He also says that subjects under DAF might provide insights into the nature and etiology of stuttering. A hypo- theses given by Webster and Lubker (1968), was that a disturbance in auditory feedback might be responsible for stuttering. There was an increase in the intensity, fundamental frequency and duration of speech when normals were asked to speak with delayed auditory feedback, (Black 1950). The findings were similar to that of a normal under bilateral application of masking noise.